Long-chain polyunsaturated fatty acids amend palmitate-induced inflammation and insulin resistance in mouse C2C12 myotubes. Issue 1 (5th October 2015) - Chen, Shiuan-Chih; Chen, Pei-Yin; Wu, Yu-Ling; Chen, Ching-Wen; Chen, Haw-Wen; Lii, Chong-Kuei; Sun, Hai-Lun; Liu, Kai-Li
Abstract : Long-chain PUFAs inhibit inflammation and insulin resistance in mouse C2C12 myotubes. Abstract : Intramuscular lipid accumulation results in inflammation, which is correlated with impaired insulin action in the skeletal muscle, an important organ for glucose uptake in the body. In this study, we explored the effects of docosahexaenoic acid (DHA), eicosapentaenoic acid (EPA), arachidonic acid (AA), and long-chain polyunsaturated fatty acids (PUFAs) on palmitic acid (PA)-induced inflammatory responses and insulin resistance in C2C12 myotubes. The mRNA expression of the pro-inflammatory cytokines interleukin-6 and tumor necrosis factor-α in PA-treated myotubes was suppressed by these three test long-chain PUFAs. Moreover, the addition of long-chain PUFAs decreased PA-induced insulin resistance as evidenced by increases in phosphorylated AKT and glucose uptake. In PA-treated myotubes, long-chain PUFAs improved glucose transporter 4 expression, basal glucose uptake without insulin, and the AMP-activated protein kinase pathway. Of note, the long-chain PUFAs obstructed the effects of PA on the activation of extracellular-signal-regulated kinase and protein kinase C-θ as well as nuclear factor-κB (NF-κB) and activator protein-1. The inhibitory effect of AA but not of DHA and EPA on PA-induced inflammation and impaired insulin action was cancelled in C2C12 myotubes transfected with a constitutively active mutant IκB kinase-β plasmid. These data suggest that long-chain PUFAs may be useful in the management of PA-induced inflammation and insulin resistance in myotubes. In addition to the NF-κB pathway, other mechanisms are involved in the health benefits of DHA and EPA in PA-treated myotubes.